"War Begins in the Minds of Men": Luther's theological anthropology and anti‐muslim polemics. Issue 3 (3rd November 2022) - Kohli, Candace L.
Abstract: The Turk is a looming figure in Martin Luther's theological imagination, emerging again and again as a rhetorical tool and historical reality in his thought and work. Yet, Luther's treatment of the Turks has received relatively little attention despite continuities in his polemical project with the Jews. In the 1540s, Luther outlined a systematic theological interrogation of Muslims' humanity and applied his own Christian theological anthropology to determine that, on the basis of belief in the Koran, Muslims do not fit the criteria to be human persons. This article examines this claim to identify ways theology and cultural bias worked in tandem to reinforce this nefarious commitment in Luther's thought.